Analysis of tax culture and compliance with tax obligations in a market in San Juan de Lurigancho, 2024. - Limaco García, Astrid Karolyn (2025)
The objective of this article is to determine the relationship between tax culture and compliance with tax obligations in the Micaela Bastidas Market Workers Association of San Juan de Lurigancho, Lima, 2024. The research is of an applied type, with a focus quantitative and descriptive level, using a non-experimental cross-sectional design. We work with the entire population, made up of 60 market traders. The information was obtained through surveys, using a 12-question questionnaire. The results showed a significant relationship between the two variables (rho=0.827) due to the absence of an appropriate tax culture, market traders have low compliance with their tax obligations, which negatively impacts compensation, affecting the company's income. public treasury. In the same way, a high significant relationship was shown with the other specific hypotheses, which were 0.333, 0.889 and 0.375 respectively. It is concluded that tax culture is significantly related to the compliance of tax obligations of merchants in the market; This responds to the need to promote a tax culture among market merchants so that they can change their attitude regarding their taxes and can fulfill their tax obligations appropriately.